Dielectric Properties of Ba0.8Ca0.2TiO3–Bi(Mg0.5, Ti0.5)O3–NaNbO3 Ceramics. Issue 12 (13th November 2013) - Zeb, Aurang; Milne, Steven J.; Damjanovic, D.
<x xml:space="preserve">Abstract</x> Ceramics in the system 0.45Ba0.8Ca0.2TiO3–(0.55−x)Bi(Mg0.5Ti0.5)O3–xNaNbO3, x = 0–0.02 were fabricated by a conventional solid‐state reaction route. X‐ray powder diffraction indicated cubic or pseudocubic symmetry for all samples. The parent 0.45Ba0.8Ca0.2TiO3–0.55Bi(Mg0.5Ti0.5)O3 composition is a relaxor dielectric with a near‐stable temperature coefficient of relative permittivity, εr = 950 ± 10% across the temperature range 80°C–600°C. Incorporation of NaNbO3 at x = 0.2 extends the lower working temperature to ≤25°C, with εr = 575% ± 15% from temperatures ≤25°C to >400°C, and tan δ < 0.025 from 25°C to 400°C. Values of dc resistivity ranged from 109 Ω·m at 250°C to 106 Ω·m at 500°C. The properties suggest that this material may be of interest for high‐temperature capacitor applications.